Revisioning John Chrysostom : new approaches, new perspectives - De Wet, Chris L., 1982-; Mayer, Wendy, 1960- (Critical Approaches to Early Christianity, 2019)
In Revisioning John Chrysostom , Chris de Wet and Wendy Mayer harness and promote a new wave of scholarship on the life and works of this famous late-antique (c. 350-407 CE) preacher. New theories from the cognitive and neurosciences, cultural and sleep studies, and history of the emotions, among others, meld with reconsideration of lapsed approaches - his debt to Graeco-Roman paideia, philosophy, and now medicine - resulting in sometimes surprising and challenging conclusions. Together the chapters produce a fresh vision of John Chrysostom that moves beyond the often negative views of the 20th century and open up substantially new vistas for exploration.